(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
The Lower Permian Hueco Group of the Doña Ana Mountains (south-central New Mexico, USA) is studied in three sections (A, B, C) located east of Leasburg, Doña Ana County. Regionally, the Hueco Group has been subdivided into four formations termed Shalem Colony, Community Pit, Robledo Mountains and Apache Dam formations; the lower three are exposed in the Doña Ana Mountains. The succession shows a shallowing upward trend from dominantly shallow, open marine conditions (Shalem Colony Fm) to increasingly restricted marine environments (Community Pit Fm) and siliciclastic influx (Robledo Mountains Formation). Sedimentation, particularly siliciclastic influx, was mainly controlled by reactivation of basement uplifts during the last pulses of the Ancestral Rocky Mountains deformation. The microfossils and microfacies of the two first formations are studied in detail here. The Shalem Colony Formation can be divided into a lower biozone with Triticites pinguis, which is Newwellian (latest Pennsylvanian, early Wolfcampian) in age, and an upper division characterized by the first occurrence of Geinitzina, and lower-middle Asselian (late early Wolfcampian) in age. By comparison with the subdivisions of the Carnic Alps (Austria), the Community Pit Formation is characterized as Sakmarian (middle Wolfcampian) in age due to the first occurrence of the genus Pseudovermiporella, and its probable complete phylogeny from Hedraites. The late Asselian is restricted to the uppermost part of the Shalem Colony and lowermost part of the Community Pit Formation. Due to the occurrence of Pseudoreichelina the Robledo Mountains Formation is dated as Artinskian (late Wolfcampian). Some bioconstructions of Archaeolithophyllum are emphasized, as well as some species of foraminifers-globivalvulinids, Miliolata and Nodosariata.